DEVELOPMENT OF CUSTOM KNEE IMPLANTS AND PROPERTY ANALYSIS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In last decade, cluster of research has been carried out in order to provide better medical treatment to human. Huge number of surgeries carried out in the world every day. In this era, medical surgery is carried out to replace or recur the damaged bone with artificial components i.e. Implant. The joint surface is recreated by replacement of knee with metal components. Authors have carried out the research to use rapid prototyping and investment casting route in medical implant. Knee implant has been selected for the present research work. Material selected is 316L Stainless Steel. To characterize the manufactured parts different tests are performed. To check the microstructure of the castings microstructure authors have used Metallurgical Microscope. Use of Rockwell Hardness Tester is implemented for testing the surface hardness. While roughness of the casting surface has checked by using surface finish tester in order to check the surface characteristics. The tensile strength of the implant material is checked on Universal Testing Machine. Authors have compared the results with present studies.